On-Sight and Red-Point Climbing: Changes in Performance and Route-Finding Ability in Male Advanced Climbers - Limonta, Eloisa; Fanchini, Maurizio; Rampichini, Susanna; Cé, Emiliano; Longo, Stefano; Coratella, Giuseppe; Esposito, Fabio (Frontiers in Psychology, 2020)
Aim In lead climbing, the ascent of the route can be defined as on-sight or red-point. On-sight is the more challenging style since it demands greater physiological and psychological commitment. The differences between the two modes in advanced climbers have not been studied much. Two essential skills needed to optimize performance, in both on-sight and in red-point climbing, are route interpretation (RI) ability and movements sequence recall. Therefore, this study aimed to compare performance between on-sight and red-point ascent in advanced climbers and evaluate how a climber’s RI ability and movement sequences recall might change before and after on-sight and red-point climbing. Methods Eighteen advanced male climbers (age 29.2 ± 4.7 years, body mass 67.8 ± 3.6 kg, stature 175.2 ± 2.4 cm, best red-point and on-sight grades 7b+/8a and 7a+/7b+, respectively) were video-recorded during the route ascent in on-sight and red-point modes to evaluate performance and to measure static and dynamic action times. RI ability and movement sequence recall were assessed before and after each climb. Level of anxiety was evaluated via a self-report questionnaire. Heart rate (fH), lactate concentration, ([La–]), and rating of perceived exertion (RPE) were detected during and after each climb. Results Compared to on-sight, an improvement in performance was observed in a red-point climb: the ascent was faster (148.7 ± 13.6 s and 179.5 ± 12.5 s, respectively, P < 0.05), smoother (significant reduction in exploratory moves and in stops times, P < 0.05), less demanding physiologically (lower fHpeak and [La–]peak, P < 0.05), and psychologically (lower RPE, cognitive and somatic anxiety and higher self-confidence, P < 0.05). The RI ability was improved in red-point versus on-sight and, in the same mode, between pre and post ascent. Conclusion Red-point climbing was found to be less demanding than on-sight, both physiologically and psychologically, under the conditions investigated by this study. Our findings suggest that RI is a trainable skill and underscore the importance of including specific techniques in training programs designed to improve interaction between perceptual, psychological, and physiological factors.